Challenges of Differentiated Instruction and Ways to Overcome Them in Primary Education - Shinjiashvili, Tamar; Akhaladze, Lia; Zurabashvili, David (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
Based on the research conducted by the authors, this paper explores the challenges of differentiated instruction in primary school classrooms. The theoretical framework of the study is built on successful educational practices related to the issue and relies on foreign, predominantly English-language materials, which formed the basis for analyzing the research results. Target group of the study: primary school teachers. Research methods: interview and observation. The study identified a number of problems. The findings revealed that for teachers, differentiation is a difficult process due to the time and resources required. It involves planning, preparing, and delivering multiple options and materials for different students. Managing classroom logistics and coordinating differentiated activities and assessments can also be challenging. Furthermore, differentiated instruction requires knowledge and skills in curriculum design, instructional strategies, assessment methods, and consideration of student diversity. Educators may also face resistance or skepticism toward traditional assumptions and practices, as well as toward the attitudes and beliefs of both teachers and students. Another challenge lies in balancing the expectations and demands of various stakeholders, including students, parents, colleagues, and school administration. Ways to Overcome the Challenges. According to the authors, successful implementation of differentiation in primary education requires teachers to have a well-defined vision, adopt a flexible approach, and foster a culture of collaboration. The following recommendations are proposed: teachers should begin working on differentiation by analyzing learning goals and standards and then use them as the foundation for adjusting content, process, product, and learning environment according to students’ needs. This creates an appropriate environment for learners. Teachers should assess students’ needs and preferences through different methods and resources, plan differentiated instruction, and adapt it to individual requirements. In addition, students should be provided with multiple options and support in various formats, modes, levels, and resources to meet their preferences. It is essential for teachers to provide clear instructions and feedback so that students can properly guide their own expectations. In the authors’ view, differentiation in primary school is a complex but crucial process for effective teaching and learning. To achieve this, teachers should ensure effective classroom organization, create flexible groups, and carefully plan the differrentiation process. Establishing clear routines, rules, and roles, and - most importantly - engaging in continuous professional growth and development will support teachers in overcoming the existing challenges.